Processing technology of multifunctional suspended ceiling

By using reinforced fiberglass mesh cloth and microcement combined with aluminum honeycomb board and fireproof board on the ceiling, the shortcomings of traditional ceiling ceilings in thermal insulation, sound insulation, fire protection and aesthetics are solved, and high performance and energy-saving are achieved multifunctional ceiling effect.

CN119221657APending Publication Date: 2024-12-31FOSHAN XINZHONGMAO ENERGY SAVING BUILDING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411403844.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Traditional ceiling ceilings have shortcomings in thermal insulation, sound insulation, fire protection and aesthetics, and the installation process is complex and energy-consuming, and lacks energy-saving solutions.

Method used

The surface of the reinforced fiberglass mesh cloth is coated with microcement, combined with aluminum honeycomb board and fireproof board, and through glue treatment and cold pressing, a ceiling ceiling integrating multi-functions is formed, including aluminum alloy frames and inorganic honeycomb cores. and high-performance microcement.

Benefits of technology

It improves the comprehensive performance of ceiling suspended ceilings, enhances aesthetics and service life, and significantly improves sound insulation, heat insulation and fire resistance, providing users with energy-saving and environmentally friendly decoration solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075972760000081
    Figure BDA0005075972760000081
Patent Text Reader

Abstract

The invention discloses a processing technology of a multifunctional suspended ceiling, and belongs to the technical field of building materials. Comprising the following steps: uniformly coating the surface of reinforced glass fiber gridding cloth with micro cement, and curing to form a micro cement layer to obtain a plate A for later use; taking the plate A, spraying glue on the surface, laying aluminum honeycomb plates on two sides, and curing to obtain a plate B; a plurality of plates B are taken, surface glue spraying treatment is carried out, stacking, cold pressing, trimming and framing are carried out in sequence, and a plate C is obtained; taking the plate C, spraying glue on the surface, laying fireproof plates on two sides, and curing to obtain a plate D; the board D is taken, surface glue spraying treatment is conducted, spunlace non-woven fabric is laid on the two faces of the board D, then the surface is evenly coated with micro cement, curing is conducted, and the multifunctional suspended ceiling with the excellent impact resistance, sound insulation, fire prevention and efflorescence resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a processing technology for a multifunctional ceiling. Background Art

[0002] Traditional ceiling systems can be roughly divided into the following categories: 1) Single-layer metal (aluminum ceiling and steel ceiling), which can only serve as ceiling decoration, and has no significant functional improvement on the thermal insulation, sound insulation and noise reduction, moisture absorption and air permeability, optical effect and fireproof and lightweight performance of the ceiling, and has no effect on the thermal insulation and sound insulation performance of the indoor space environment under the roof; 2) Although the aluminum honeycomb composite panel ceiling also has certain thermal insulation and sound insulation functions, its actual thermal insulation and sound insulation functions are not ideal, because the upper and lower aluminum panels of the aluminum honeycomb panel and the aluminum honeycomb core in the middle cannot cut off the cold and heat bridges and sound bridges when bonded by two-component colloid, and cold air, hot air and sound can still be connected through the aluminum honeycomb core in the middle and the upper and lower aluminum panels, resulting in the inability to truly cut off the cold and heat bridges and sound bridges, and the ideal thermal insulation and sound insulation effect cannot be achieved. It is necessary to repeat the thermal insulation or sound insulation project on the indoor ceiling under the roof for a second time, which is a semi-energy-consuming ceiling panel system, which is very unsatisfactory. Energy saving, but installation and construction are labor-intensive, time-consuming and labor-intensive; 3) SPC stone plastic ceiling panels or SMC thermosetting resin ceiling panels only emphasize their decorative properties. Although they can be flame-retardant at level B1, the thick smoke and toxic smoke during combustion are major hidden dangers that cannot be eliminated forever. Once a flame burns, the thick smoke and toxic smoke released quickly will be fatal quickly, and there is no significant improvement in economic benefits in terms of energy saving; 4) Paper-faced gypsum board ceiling panels, although they have heat insulation, air isolation and noise reduction properties, It is necessary to pre-install a light steel keel structure on the ceiling, and then install a paper-faced gypsum board ceiling system. The current construction process is complicated, dusty, noisy, and polluting, and there is a lot of decoration waste, which wastes a lot of manpower, material, and financial resources; the traditional high-density calcium silicate ceiling system can also achieve the performance of fireproofing, heat insulation, sound insulation, and noise reduction, but the high-density calcium silicate board is brittle and fragile due to its high density, heavy weight, strong rigidity, and when it encounters high-temperature flames, the calcium silicate board surface will burst and fragments will injure people. Therefore, it is particularly urgent to develop a new ceiling system that integrates multiple functions. Summary of the invention

[0003] The purpose of the invention is to provide a multifunctional ceiling processing technology for improving the comprehensive performance of the ceiling.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A processing technology for a multifunctional ceiling comprises the following steps:

[0006] S1. Evenly coat the surface of the reinforced glass fiber mesh with microcement, solidify it to form a microcement layer, and obtain a plate A for standby use;

[0007] S2, taking the plate A, treating the surface with glue, laying aluminum honeycomb panels on both sides, and curing to obtain plate B;

[0008] S3, taking a number of the plates B, applying glue on the surface, stacking, cold pressing, trimming, and assembling the plates in sequence to obtain plates C;

[0009] S4, taking the board C, applying glue on the surface, laying fireproof boards on both sides, and curing to obtain board D;

[0010] S5. Take the board D, treat the surface with glue, lay spunlace non-woven fabrics on both sides, and then evenly coat the surface with microcement and solidify it to obtain the multifunctional ceiling.

[0011] As a preferred technical solution of the present invention, the preparation method of the microcement comprises the following steps:

[0012] A1, mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, ultrasonically disperse for 10-20 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 50-60°C for 10-15 hours, centrifuge, wash the solid phase, dry and grind to obtain material A;

[0013] A2, taking the material A and anhydrous ethanol, mixing, ultrasonically dispersing for 15-25 minutes, adding KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stirring for 10-15 hours, centrifuging, washing, drying, and grinding the solid phase to obtain material B;

[0014] A3. In a nitrogen atmosphere, mix 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide, stir at 60°C for 3-4h, filter and take the liquid phase to obtain material C;

[0015] A4, take pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mix them, and stir them ultrasonically for 30-40 minutes to obtain material D;

[0016] A5. Take the material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water and water reducing agent, mix them and stir them evenly to obtain the microcement.

[0017] As a preferred technical solution of the present invention, in step A1, the dosage ratio of the carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water, and tetraethyl orthosilicate is 1.4-1.6 g: 30-40 mL: 150 mL: 16-18 mL: 3-4 mL; the concentration of the ammonia water is 14.8 mol / L.

[0018] As a preferred technical solution of the present invention, in step A2, the mass ratio of material A, anhydrous ethanol, KH550, and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.6-0.8:30-40:0.1-0.12:0.08-0.11.

[0019] As a preferred technical solution of the present invention, in step A3, the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide is 22-26:175-185:28-30:0.2-0.4.

[0020] As a preferred technical solution of the present invention, in step A4, the mass ratio of pentaerythritol tetrakis(3-mercaptopropionate) ester to 4-dimethylaminopyridine is 45-49:0.5-0.8.

[0021] As a preferred technical solution of the present invention, in step A5, the mass ratio of material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water, and water reducer is 0.1-0.2: 5.5-6.3: 4.2-4.8: 1-2: 85-92: 10-12: 5-6: 30-40: 1-2.

[0022] As a preferred technical solution of the present invention, the method for preparing the fireproof board comprises the following steps:

[0023] B1, take polyethylene glycol monomethyl ether and toluene diisocyanate, mix, stir at 35-45 ° C for 2-3 hours, heat to 70-75 ° C and continue stirring for 1-2 hours to obtain material E;

[0024] B2, taking the material E and epoxy resin E51, mixing them, stirring at 75-80° C. for 3-4 hours, to obtain material F;

[0025] B3, mix ethyl orthosilicate and methyltriethoxysilane, stir for 30-40 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 20-30 hours to obtain material G;

[0026] B4, taking the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water, mixing, ball milling for 2-3 hours, spray drying, curing, debinding, sintering, and obtaining material H;

[0027] B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, animal protein foaming agent, plant adhesive, citric acid, sodium phosphate and sodium sulfate, perform ultrasonic dispersion for 1-2 hours, transfer to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming of four sides to obtain the fireproof board.

[0028] As a preferred technical solution of the present invention, in step B1, the mass ratio of the polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; and the relative molecular mass of the polyethylene glycol monomethyl ether is 650.

[0029] As a preferred technical solution of the present invention, in step B2, the mass ratio of the material E to the epoxy resin E51 is 8.8-9.2:0.8-1.2; and the epoxy value of the epoxy resin E51 is 0.51 mol / 100g.

[0030] As a preferred technical solution of the present invention, in step B3, the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3-4: 1-1.2: 2-3: 2-3: 0.2-0.4.

[0031] As a preferred technical solution of the present invention, in step B4, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water is 5-8:10-12:8-10:15-18:20-30:1-2:40-50.

[0032] As a preferred technical solution of the present invention, in step B5, the mass ratio of material F, material H, curing agent XY-401, DMP-30 curing agent, animal protein foaming agent, plant adhesive, citric acid, sodium phosphate and sodium sulfate is 10-15:20-30:0.4-0.6:0.2-0.3:0.1-0.2:1-2:1.2-1.4:0.7-0.9:1-1.2.

[0033] Beneficial effects of the present invention:

[0034] The present invention discloses a processing technology for a multifunctional ceiling, which integrates an aluminum alloy frame structure, an inorganic honeycomb core lightweight type, a high-performance microcement functional type, and an excellent fireproof board to form an integrated multifunctional ceiling. It not only improves the aesthetics and service life of the ceiling, but also greatly enhances its functionality, providing users with a beautiful and practical interior decoration solution. DETAILED DESCRIPTION

[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0036] Example 1

[0037] A processing technology for a multifunctional ceiling comprises the following steps:

[0038] S1. Take a reinforced glass fiber mesh cloth (specifically a polytetrafluoroethylene-coated glass fiber mesh cloth, purchased from Wuxi Fushide High-Tech Special Materials Manufacturing Co., Ltd.) and evenly coat the surface with microcement, and cure it at 100° C. for 6 hours to form a microcement layer with a thickness of 3 mm to obtain a plate A for standby use;

[0039] S2, take the plate A, treat the surface with glue, lay aluminum honeycomb panels (purchased from Shandong Jinjieli Material Technology Co., Ltd.) on both sides, and cure at 30° C. for 20 hours to obtain plate B;

[0040] S3, take 8 pieces of the plate B, treat the surface with glue, stack them in sequence, cold press (working pressure is 4 tons, pressing for 2 hours), trim them, and frame them to obtain plate C;

[0041] S4, take the board C, treat the surface with glue, lay fireproof boards on both sides, and cure at 30°C for 20h to obtain board D;

[0042] S5. Take the board D, treat the surface with glue, lay spunlace non-woven fabrics (specifically PP spunlace non-woven fabrics, purchased from Dongying Yinong Non-woven Fabric Co., Ltd.) on both sides, and then evenly coat the surface with microcement, and cure it at 100° C. for 6 hours to obtain the multifunctional ceiling;

[0043] The glue used for the glue spraying treatment is a two-component polyurethane sealant purchased from Zhejiang Hangtongzhou New Materials Technology Co., Ltd., model J2033.

[0044] The preparation method of the microcement comprises the following steps:

[0045] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse them ultrasonically for 10 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 50°C for 10 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.4g:30mL:150mL:16mL:3mL; the concentration of ammonia water is 14.8mol / L;

[0046] A2, take the material A and anhydrous ethanol, mix them, ultrasonically disperse them for 15 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 10 hours, centrifuge, wash the solid phase, dry, grind, and obtain material B; the mass ratio of the material A, anhydrous ethanol, KH550, 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.6:30:0.1:0.08;

[0047] A3. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 3h, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 22:175:28:0.2;

[0048] A4, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing them, and ultrasonically stirring for 30 minutes to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine is 45:0.5;

[0049] A5. Mix the material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water and water reducer is 0.1:5.5:4.2:1:85:10:5:30:1;

[0050] The cement is P·O 42.5R Tianshan ordinary Portland cement, purchased from Xinjiang Midong Tianshan Cement Co., Ltd.;

[0051] The chemical composition content of the lithium slag is measured as shown in Table 1 below:

[0052] Table 1 Chemical composition of lithium slag (mass fraction) %

[0053]

[0054] The aggregate was purchased from Henan Fengkai Refractory Material Co., Ltd., CAS No. 65997-16-2;

[0055] The water reducing agent was purchased from Wujiaqu Gehui New Materials Co., Ltd.

[0056] The preparation method of the fireproof board comprises the following steps:

[0057] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 35°C for 2h, heat to 70°C and continue stirring for 1h to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0058] B2. Mix the material E and epoxy resin E51, stir at 75° C. for 3 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 8.8:0.8; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0059] B3, take tetraethyl orthosilicate and methyltriethoxysilane, mix them, stir for 30 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 20 hours, and obtain material G; the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3:1:2:2:0.2;

[0060] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 2 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 5:10:8:15:20:1:40;

[0061] The spray drying conditions are nozzle temperature of 130°C, feed rate of 160mL / h, and spray pressure of 0.2kPa;

[0062] The curing temperature is 150° C. and the curing time is 1 hour;

[0063] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0064] The sintering refers to keeping the temperature at 1080°C for 2h;

[0065] B5. Take the material F, material H, curing agent XY-401 (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), DMP-30 curing agent (purchased from Jiangsu Xinsu New Materials Co., Ltd.), animal protein foaming agent (specific product model is foaming agent TR-B, CAS No. 80-51-3, purchased from Luoyang Tongrun Information Technology Co., Ltd.), plant adhesive (specifically gum arabic, purchased from Shanghai McLean Biochemical Technology Co., Ltd.), citric acid, sodium phosphate, and sodium sulfate, mix, ultrasonically disperse for 1-2 hours, transfer to the mold for spreading, rolling, stacking, initial setting, demolding, secondary curing, drying, and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, animal protein foaming agent, plant adhesive, citric acid, sodium phosphate, and sodium sulfate is 10:20:0.4:0.2:0.1:1:1.2:0.7:1.

[0066] Example 2

[0067] A processing technology for a multifunctional ceiling comprises the following steps:

[0068] S1. Take a polytetrafluoroethylene-coated glass fiber mesh cloth, evenly coat the surface with microcement, and cure it at 105° C. for 7 hours to form a microcement layer with a thickness of 4 mm to obtain a plate A for standby use;

[0069] S2, take the plate A, treat the surface with glue, lay aluminum honeycomb panels on both sides, and cure at 35° C. for 25 hours to obtain plate B;

[0070] S3, take 9 pieces of the plate B, treat the surface with glue, stack them in sequence, cold press (working pressure is 5 tons, pressing for 3 hours), trim them, and frame them to obtain plate C;

[0071] S4, take the board C, treat the surface with glue, lay fireproof boards on both sides, and cure at 35° C. for 25 hours to obtain board D;

[0072] S5. Take the board D, treat the surface with glue, lay PP spunlace non-woven fabric on both sides, and then evenly coat the surface with microcement, and cure it at 105° C. for 7 hours to obtain the multifunctional ceiling.

[0073] The preparation method of the microcement comprises the following steps:

[0074] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse them ultrasonically for 15 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 55°C for 12 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.5g:35mL:150mL:17mL:3.5mL; the concentration of ammonia water is 14.8mol / L;

[0075] A2, take the material A and anhydrous ethanol, mix them, ultrasonically disperse them for 20 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 12 hours, centrifuge, wash the solid phase, dry, grind, and obtain material B; the mass ratio of the material A, anhydrous ethanol, KH550, 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.7:35:0.11:0.095;

[0076] A3. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 3.5h, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 24:180:29:0.3;

[0077] A4, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing them, and ultrasonically stirring for 35 minutes to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine is 47:0.65;

[0078] A5. Mix the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer is 0.15:5.9:4.5:1.5:89:11:5.5:35:1.5.

[0079] The preparation method of the fireproof board comprises the following steps:

[0080] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 40°C for 2.5 hours, heat to 72°C and continue stirring for 1.5 hours to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0081] B2. Mix the material E and epoxy resin E51, stir at 78° C. for 3.5 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.0:1.0; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0082] B3, take tetraethyl orthosilicate and methyltriethoxysilane, mix them, stir for 35 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 25 hours, and obtain material G; the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3.5:1.1:2.5:2.5:0.3;

[0083] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 2.5 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 6.5:11:9:17:25:1.5:45;

[0084] The spray drying conditions are nozzle temperature of 135°C, feed rate of 165mL / h, and spray pressure of 0.23kPa;

[0085] The curing temperature is 150°C and the curing time is 1.5h;

[0086] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0087] The sintering refers to keeping the temperature at 1110°C for 2.2h;

[0088] B5. Take the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate, mix them, ultrasonically disperse them for 1.5 hours, transfer them to the mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying, and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate is 13:25:0.5:0.25:0.15:1.5:1.3:0.8:1.1.

[0089] Example 3

[0090] A processing technology for a multifunctional ceiling comprises the following steps:

[0091] S1. Take a polytetrafluoroethylene-coated glass fiber mesh cloth, evenly coat the surface with microcement, and cure it at 110° C. for 8 h to form a microcement layer with a thickness of 5 mm to obtain a plate A for standby use;

[0092] S2, take the plate A, treat the surface with glue, lay aluminum honeycomb panels on both sides, and cure at 40° C. for 30 hours to obtain plate B;

[0093] S3, take 10 pieces of the plate B, treat the surface with glue, stack them in sequence, cold press (working pressure is 6 tons, pressing for 4 hours), trim them, and frame them to obtain plate C;

[0094] S4, take the board C, treat the surface with glue, lay fireproof boards on both sides, and cure at 40° C. for 30 hours to obtain board D;

[0095] S5. Take the board D, treat the surface with glue, lay PP spunlace non-woven fabric on both sides, and then evenly coat the surface with microcement, and cure it at 110° C. for 8 hours to obtain the multifunctional ceiling.

[0096] The preparation method of the microcement comprises the following steps:

[0097] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse by ultrasonic for 20 min, add tetraethyl orthosilicate, heat and stir in a water bath at 60°C for 15 h, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.6 g: 40 mL: 150 mL: 18 mL: 4 mL; the concentration of ammonia water is 14.8 mol / L;

[0098] A2, take the material A and anhydrous ethanol, mix them, ultrasonically disperse them for 25 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 15 hours, centrifuge, wash the solid phase, dry, grind, and obtain material B; the mass ratio of the material A, anhydrous ethanol, KH550, 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.8:40:0.12:0.11;

[0099] A3. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 4 hours, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 26:185:30:0.4;

[0100] A4, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing them, and ultrasonically stirring them for 40 minutes to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester to 4-dimethylaminopyridine is 49:0.8;

[0101] A5. Mix the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer is 0.2:6.3:4.8:2:92:12:6:40:2.

[0102] The preparation method of the fireproof board comprises the following steps:

[0103] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 45°C for 3h, heat to 75°C and continue stirring for 2h to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0104] B2. Mix the material E and epoxy resin E51, stir at 80° C. for 4 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.2:1.2; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0105] B3, mix ethyl orthosilicate and methyltriethoxysilane, stir for 40 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 30 hours to obtain material G; the mass ratio of ethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 4:1.2:3:3:0.4;

[0106] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 3 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 8:12:10:18:30:2:50;

[0107] The spray drying conditions are nozzle temperature of 140°C, feed rate of 170 mL / h, and spray pressure of 0.25 kPa;

[0108] The curing temperature is 150°C and the curing time is 2h;

[0109] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0110] The sintering refers to keeping the temperature at 1150°C for 2.5 hours;

[0111] B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate, perform ultrasonic dispersion for 2 hours, transfer the mixture to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate is 15:30:0.6:0.3:0.2:2:1.4:0.9:1.2.

[0112] Comparative Example 1

[0113] The difference from Example 2 is that the preparation method of the microcement comprises the following steps:

[0114] A1. Mix carboxylated double-walled carbon nanotubes, silicon dioxide and anhydrous ethanol, perform ultrasonic dispersion for 20 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 12 hours, centrifuge, wash the solid phase, dry and grind to obtain material B; the mass ratio of carboxylated double-walled carbon nanotubes, silicon dioxide, anhydrous ethanol, KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.4:0.3:35:0.11:0.095;

[0115] A2. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 3.5h, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 24:180:29:0.3;

[0116] A3, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing, ultrasonic stirring for 35 minutes, to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine is 47:0.65;

[0117] A4. Mix the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material B, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer is 0.15:5.9:4.5:1.5:89:11:5.5:35:1.5.

[0118] Comparative Example 2

[0119] The difference from Example 2 is that the preparation method of the microcement comprises the following steps:

[0120] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse them ultrasonically for 15 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 55°C for 12 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.5g:35mL:150mL:17mL:3.5mL; the concentration of ammonia water is 14.8mol / L;

[0121] A2. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 3.5h, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 24:180:29:0.3;

[0122] A3, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing, ultrasonic stirring for 35 minutes, to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine is 47:0.65;

[0123] A4. Mix the material A, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material A, material C, material D, cyclohexanedimethanol, cement, lithium slag, aggregate, deionized water and water reducer is 0.15:5.9:4.5:1.5:89:11:5.5:35:1.5.

[0124] Comparative Example 3

[0125] The difference from Example 2 is that the preparation method of the microcement comprises the following steps:

[0126] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse them ultrasonically for 15 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 55°C for 12 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.5g:35mL:150mL:17mL:3.5mL; the concentration of ammonia water is 14.8mol / L;

[0127] A2, take the material A and anhydrous ethanol, mix them, ultrasonically disperse them for 20 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 12 hours, centrifuge, wash the solid phase, dry, grind, and obtain material B; the mass ratio of the material A, anhydrous ethanol, KH550, 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.7:35:0.11:0.095;

[0128] A3. In a nitrogen atmosphere, 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide were mixed, stirred at 60°C for 3.5h, filtered, and the liquid phase was taken to obtain material C; the mass ratio of 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide was 24:180:29:0.3;

[0129] A4, taking pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mixing them, and ultrasonically stirring for 35 minutes to obtain material D; the mass ratio of pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine is 47:0.65;

[0130] A5. Mix the material B, material C, material D, cyclohexanedimethanol ester, cement, aggregate, deionized water and water reducer, and stir evenly to obtain the microcement; the mass ratio of the material B, material C, material D, cyclohexanedimethanol ester, cement, aggregate, deionized water and water reducer is 0.15:5.9:4.5:1.5:89:5.5:35:1.5.

[0131] Comparative Example 4

[0132] The difference from Example 2 is that the preparation method of the microcement comprises the following steps:

[0133] A1. Mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, disperse them ultrasonically for 15 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 55°C for 12 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; the ratio of carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1.5g:35mL:150mL:17mL:3.5mL; the concentration of ammonia water is 14.8mol / L;

[0134] A2, take the material A and anhydrous ethanol, mix them, ultrasonically disperse them for 20 minutes, add KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stir for 12 hours, centrifuge, wash the solid phase, dry, grind, and obtain material B; the mass ratio of the material A, anhydrous ethanol, KH550, 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.7:35:0.11:0.095;

[0135] A3. Mix the material B, cement, lithium slag, aggregate, deionized water and water reducing agent, and stir evenly to obtain the microcement; the mass ratio of the material B, cement, lithium slag, aggregate, deionized water and water reducing agent is 0.15:89:11:5.5:35:1.5.

[0136] Comparative Example 5

[0137] The difference from Example 2 is that the method for preparing the fireproof board comprises the following steps:

[0138] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 40°C for 2.5 hours, heat to 72°C and continue stirring for 1.5 hours to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0139] B2. Mix the material E and epoxy resin E51, stir at 78° C. for 3.5 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.0:1.0; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0140] B3, take tetraethyl orthosilicate and methyltriethoxysilane, mix them, stir for 35 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 25 hours, and obtain material G; the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3.5:1.1:2.5:2.5:0.3;

[0141] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 2.5 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 6.5:11:9:17:25:1.5:45;

[0142] The spray drying conditions are nozzle temperature of 135°C, feed rate of 165mL / h, and spray pressure of 0.23kPa;

[0143] The curing temperature is 150°C and the curing time is 1.5h;

[0144] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0145] The sintering refers to keeping the temperature at 1110°C for 2.2h;

[0146] B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, sodium phosphate and sodium sulfate, perform ultrasonic dispersion for 1.5 hours, transfer the mixture to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, sodium phosphate and sodium sulfate is 13:25:0.5:0.25:0.15:1.5:2.1:1.1.

[0147] Comparative Example 6

[0148] The difference from Example 2 is that the method for preparing the fireproof board comprises the following steps:

[0149] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 40°C for 2.5 hours, heat to 72°C and continue stirring for 1.5 hours to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0150] B2. Mix the material E and epoxy resin E51, stir at 78° C. for 3.5 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.0:1.0; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0151] B3, take tetraethyl orthosilicate and methyltriethoxysilane, mix them, stir for 35 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 25 hours, and obtain material G; the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3.5:1.1:2.5:2.5:0.3;

[0152] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 2.5 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 6.5:11:9:17:25:1.5:45;

[0153] The spray drying conditions are nozzle temperature of 135°C, feed rate of 165mL / h, and spray pressure of 0.23kPa;

[0154] The curing temperature is 150°C and the curing time is 1.5h;

[0155] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0156] The sintering refers to keeping the temperature at 1110°C for 2.2h;

[0157] B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid and sodium sulfate, perform ultrasonic dispersion for 1.5 hours, transfer the mixture to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid and sodium sulfate is 13:25:0.5:0.25:0.15:1.5:1.3:1.9.

[0158] Comparative Example 7

[0159] The difference from Example 2 is that the method for preparing the fireproof board comprises the following steps:

[0160] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 40°C for 2.5 hours, heat to 72°C and continue stirring for 1.5 hours to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0161] B2. Mix the material E and epoxy resin E51, stir at 78° C. for 3.5 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.0:1.0; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0162] B3, take tetraethyl orthosilicate and methyltriethoxysilane, mix them, stir for 35 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 25 hours, and obtain material G; the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water and acetic acid is 3.5:1.1:2.5:2.5:0.3;

[0163] B4. Mix the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water, ball mill for 2.5 hours, spray dry, solidify, debind and sinter to obtain material H; the mass ratio of the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000 and deionized water is 6.5:11:9:17:25:1.5:45;

[0164] The spray drying conditions are nozzle temperature of 135°C, feed rate of 165mL / h, and spray pressure of 0.23kPa;

[0165] The curing temperature is 150°C and the curing time is 1.5h;

[0166] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0167] The sintering refers to keeping the temperature at 1110°C for 2.2h;

[0168] B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid and sodium phosphate, perform ultrasonic dispersion for 1.5 hours, transfer the mixture to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid and sodium phosphate is 13:25:0.5:0.25:0.15:1.5:1.3:1.9.

[0169] Comparative Example 8

[0170] The difference from Example 2 is that the method for preparing the fireproof board comprises the following steps:

[0171] B1. Mix polyethylene glycol monomethyl ether and toluene diisocyanate, stir at 40°C for 2.5 hours, heat to 72°C and continue stirring for 1.5 hours to obtain material E; the mass ratio of polyethylene glycol monomethyl ether to toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650;

[0172] B2. Mix the material E and epoxy resin E51, stir at 78° C. for 3.5 h, and obtain material F; the mass ratio of the material E to the epoxy resin E51 is 9.0:1.0; the epoxy value of the epoxy resin E51 is 0.51 mol / 100g;

[0173] B3, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water were mixed, ball milled for 2.5 hours, spray dried, solidified, debinded, and sintered to obtain material H; the mass ratio of magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water was 11:9:17:25:1.5:45;

[0174] The spray drying conditions are nozzle temperature of 135°C, feed rate of 165mL / h, and spray pressure of 0.23kPa;

[0175] The curing temperature is 150°C and the curing time is 1.5h;

[0176] The debinding process refers to heating the room temperature to 500°C at a rate of 5°C / min and keeping the temperature for 3 hours to debind;

[0177] The sintering refers to keeping the temperature at 1110°C for 2.2h;

[0178] B4. Take the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate, mix them, ultrasonically disperse them for 1.5 hours, transfer them to the mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying, and trimming the four sides to obtain the fireproof board; the mass ratio of the material F, material H, curing agent XY-401, DMP-30 curing agent, foaming agent TR-B, gum arabic, citric acid, sodium phosphate and sodium sulfate is 13:25:0.5:0.25:0.15:1.5:1.3:0.8:1.1.

[0179] Comparative Example 9

[0180] The difference from Example 2 is that in the preparation process of the fireproof board, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water in step B4 is 6.5:0:20:17:25:1.5:45.

[0181] Comparative Example 10

[0182] The difference from Example 2 is that in the preparation process of the fireproof board, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water in step B4 is 6.5:20:0:17:25:1.5:45.

[0183] Comparative Example 11

[0184] The difference from Example 2 is that in the preparation process of the fireproof board, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water in step B4 is 6.5:11:9:0:42:1.5:45.

[0185] Comparative Example 12

[0186] The difference from Example 2 is that in the preparation process of the fireproof board, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water in step B4 is 6.5:11:9:42:0:1.5:45.

[0187] Comparative Example 13

[0188] The difference from Example 2 is that the processing technology of the multifunctional ceiling comprises the following steps:

[0189] S1. Take a polytetrafluoroethylene-coated glass fiber mesh cloth, evenly coat the surface with microcement, and cure it at 105° C. for 7 hours to form a microcement layer with a thickness of 4 mm to obtain a plate A for standby use;

[0190] S2, take the plate A, treat the surface with glue, lay aluminum honeycomb panels on both sides, and cure at 35° C. for 25 hours to obtain plate B;

[0191] S3, take 9 pieces of the plate B, treat the surface with glue, stack them in sequence, cold press (working pressure is 5 tons, pressing for 3 hours), trim them, and frame them to obtain plate C;

[0192] S4. Take the board C, treat the surface with glue, lay fireproof boards on both sides, and cure it at 35° C. for 25 hours to obtain the multifunctional ceiling.

[0193] Performance Testing

[0194] Test Example 1

[0195] The ceilings prepared in Examples 1-3 and Comparative Examples 1, 2, 4, and 9-12 were measured for weighted sound insulation according to the standard GB / T 50121-2005 building sound insulation evaluation standard. The test results are shown in Table 2 below.

[0196] Table 2

[0197] Weighted sound insulation(dB) Example 1 33.47 Example 2 33.58 Example 3 33.52 Comparative Example 1 27.38 Comparative Example 2 29.21 Comparative Example 4 26.37 Comparative Example 9 31.33 Comparative Example 10 31.28 Comparative Example 11 31.74 Comparative Example 12 31.55

[0198] It can be seen from Table 2 that the ceilings prepared by Examples 1-3 of the present application have excellent sound insulation effects; in Comparative Example 1, only the carbon nanotubes and silica are physically mixed, resulting in agglomeration and poor dispersibility, resulting in poor sound absorption effects; in Comparative Example 2, the carbon nanotubes loaded with silica are not modified, resulting in difficulty in forming a highly cross-linked network structure as a cross-linking support site during the cross-linking and curing of the resin, resulting in reduced sound insulation effects; in Comparative Example 4, no highly cross-linked resin emulsion is added, resulting in reduced sound insulation effects; Comparative Examples 9-12 show that magnesium oxide powder, magnesium sulfate powder, perlite powder, and kaolin are added in the present application, and a hollow microsphere structure is obtained through the synergistic effect of the four, which has good sound insulation and sound absorption properties, the porous structure of perlite can effectively absorb sound waves, the layered structure of kaolin contributes to the scattering and absorption of sound waves, magnesium sulfate and magnesium oxide increase the damping properties of the material, slow down the propagation speed of sound waves, and further enhance the sound absorption effect.

[0199] Test Example 2

[0200] The ceilings prepared in Examples 1-3 and Comparative Examples 1-7 were tested for their anti-halogenation performance. The test results are shown in Table 3 below.

[0201] Table 3

[0202] Evaluation of anti-halogen performance Example 1 No water drops, no moisture Example 2 No water drops, no moisture Example 3 No water drops, no moisture Comparative Example 1 Trace water droplets, slight moisture Comparative Example 2 Trace water droplets, slight moisture Comparative Example 3 Trace water droplets, slight moisture Comparative Example 4 Trace water droplets, slight moisture Comparative Example 5 Trace water droplets, slight moisture Comparative Example 6 Trace water droplets, slight moisture Comparative Example 7 Trace water droplets, slight moisture

[0203] It can be seen from Table 3 that the ceilings prepared in Examples 1-3 of the present application have excellent anti-halogen return performance; in Comparative Example 1, the carbon nanotubes and silica are physically mixed, and the hydrophobicity is poor, resulting in halogen return; in Comparative Example 2, the carbon nanotubes loaded with silica are not surface hydrophobically modified, resulting in halogen return; in Comparative Example 3, lithium slag is not added to fill the pores of the carbon nanotubes, resulting in structural voids and halogen return; in Comparative Example 4, a thiol-acrylate-epoxy resin hydrophobic structure with low surface energy is not constructed, resulting in reduced hydrophobic performance and halogen return; in Comparative Examples 5-7, the formation of the internal magnesium hydroxide phase is not suppressed by the synergistic effect of citric acid, sodium phosphate and sodium sulfate, resulting in halogen return.

[0204] Test Example 3

[0205] The ceilings prepared in Examples 1-3 and Comparative Examples 9-13 were tested for fire resistance according to standards GB 8624-2006 and GB / T20284-2006. The test results are shown in Table 4 below.

[0206] Table 4

[0207] Flame retardant Fire resistance Example 1 A1 No burning droplets within 800s Example 2 A1 No burning droplets within 800s Example 3 A1 No burning droplets within 800s Comparative Example 9 A2 No burning droplets within 700s Comparative Example 10 A2 No burning droplets within 700s Comparative Example 11 A2 No burning droplets within 700s Comparative Example 12 A2 No burning droplets within 700s Comparative Example 13 A3 No burning droplets within 500s

[0208] It can be seen from Table 4 that the ceilings prepared in Examples 1-3 of the present application have good flame retardant properties. The fireproof board is prepared by a composite material composed of magnesium oxide powder, magnesium sulfate powder, perlite powder and kaolin, and its excellent flame retardant effect is mainly achieved through the synergistic effect of these materials. Magnesium oxide has good temperature resistance and chemical stability, can maintain its structure unchanged at high temperatures, and does not release harmful gases when burned. The presence of magnesium sulfate can improve the fire resistance of the material and help to reduce the temperature of the surface of the material. Perlite has excellent thermal insulation and heat insulation properties, which helps to block heat conduction. Kaolin is a silicon-aluminum mineral that can form a stable refractory layer at high temperatures to slow down the spread of flames. The combination of these materials provides a solid matrix to ensure its stability and fire resistance in high temperature environments; microcement is coated on the surface of the fireproof board to synergistically improve the fire retardant properties of the ceiling.

[0209] Test Example 4

[0210] The impact strength test of Examples 1-3, Comparative Examples 1-4 and Comparative Example 8 was carried out according to standard GB / T 33544-2017. The test results are shown in Table 5 below.

[0211] Table 5

[0212] <![CDATA[Maximum load F at failure c (kN)]]> Example 1 41.9884 Example 2 41.9915 Example 3 41.9902 Comparative Example 1 38.2145 Comparative Example 2 39.5217 Comparative Example 3 39.0147 Comparative Example 4 38.8766 Comparative Example 8 38.4125

[0213] It can be seen from Table 5 that the ceilings prepared in Examples 1-3 of the present application have good impact resistance; the lamellar structure of silicon dioxide loaded on the surface of carbon nanotubes is uniformly dispersed in the cross-linked resin to form a highly cross-linked structure, thereby improving the impact resistance; by adding lithium slag to fill the cross-linked pores, the density is increased, and the impact resistance is further improved; in the process of preparing hollow microspheres by sintering magnesium oxide powder, magnesium sulfate powder, perlite powder, and kaolin, the addition of silicon oxide polymer is beneficial to filling the surface pores of the hollow microspheres during the sintering process of the hollow microspheres, and improving their density strength and improving the impact resistance.

[0214] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A multifunctional ceiling processing technology, characterized in that: The following steps are involved: S1. Evenly coat the surface of the reinforced glass fiber mesh with microcement, solidify it to form a microcement layer, and obtain a plate A for standby use; S2, taking the plate A, treating the surface with glue, laying aluminum honeycomb panels on both sides, and curing to obtain plate B; S3, taking a number of the plates B, applying glue on the surface, stacking, cold pressing, trimming, and assembling the plates in sequence to obtain plates C; S4, taking the board C, applying glue on the surface, laying fireproof boards on both sides, and curing to obtain board D; S5. Take the board D, treat the surface with glue, lay spunlace non-woven fabrics on both sides, and then evenly coat the surface with microcement and solidify it to obtain the multifunctional ceiling.

2. A multifunctional ceiling processing technology according to claim 1, characterized in that: The preparation method of the microcement comprises the following steps: A1, mix carboxylated double-walled carbon nanotubes, isopropanol, deionized water and ammonia water, ultrasonically disperse for 10-20 minutes, add tetraethyl orthosilicate, heat and stir in a water bath at 50-60°C for 10-15 hours, centrifuge, wash the solid phase, dry and grind to obtain material A; A2, taking the material A and anhydrous ethanol, mixing, ultrasonically dispersing for 15-25 minutes, adding KH550 and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane, stirring for 10-15 hours, centrifuging, washing, drying, and grinding the solid phase to obtain material B; A3. In a nitrogen atmosphere, mix 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide, stir at 60°C for 3-4h, filter and take the liquid phase to obtain material C; A4, take pentaerythritol tetrakis (3-mercaptopropionic acid) ester and 4-dimethylaminopyridine, mix them, and stir them ultrasonically for 30-40 minutes to obtain material D; A5. Mix the material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water and water reducing agent, and stir evenly to obtain the microcement.

3. The processing technology of a multifunctional ceiling according to claim 2 is characterized in that: In step A1, the ratio of the carboxylated double-walled carbon nanotubes, isopropanol, deionized water, ammonia water, and tetraethyl orthosilicate is 1.4-1.6 g: 30-40 mL: 150 mL: 16-18 mL: 3-4 mL; the concentration of the ammonia water is 14.8 mol / L.

4. The processing technology of a multifunctional ceiling according to claim 2 is characterized in that: In step A2, the mass ratio of material A, anhydrous ethanol, KH550, and 1H,1H,2H,2H-heptadecafluorodecyltrimethoxysilane is 0.6-0.8:30-40:0.1-0.12:0.08-0.

11.

5. The processing technology of a multifunctional ceiling according to claim 2 is characterized in that: In step A3, the mass ratio of the 2,5-furan dimethanol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide is 22-26:175-185:28-30:0.2-0.

4.

6. The processing technology of a multifunctional ceiling according to claim 2 is characterized in that: In step A4, the mass ratio of pentaerythritol tetrakis(3-mercaptopropionate) ester to 4-dimethylaminopyridine is 45-49:0.5-0.

8.

7. The processing technology of a multifunctional ceiling according to claim 2 is characterized in that: In step A5, the mass ratio of material B, material C, material D, cyclohexanedimethanol ester, cement, lithium slag, aggregate, deionized water and water reducing agent is 0.1-0.2:5.5-6.3:4.2-4.8:1-2:85-92:10-12:5-6:30-40:1-2.

8. The processing technology of a multifunctional ceiling according to claim 1 is characterized in that: The preparation method of the fireproof board comprises the following steps: B1, take polyethylene glycol monomethyl ether and toluene diisocyanate, mix, stir at 35-45 ° C for 2-3 hours, heat to 70-75 ° C and continue stirring for 1-2 hours to obtain material E; B2, taking the material E and epoxy resin E51, mixing them, stirring at 75-80° C. for 3-4 hours, to obtain material F; B3, mix ethyl orthosilicate and methyltriethoxysilane, stir for 30-40 minutes, add anhydrous ethanol, deionized water and acetic acid, stir for 20-30 hours to obtain material G; B4, taking the material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water, mixing, ball milling for 2-3 hours, spray drying, curing, debinding, sintering, and obtaining material H; B5. Mix the material F, material H, curing agent XY-401, DMP-30 curing agent, animal protein foaming agent, plant adhesive, citric acid, sodium phosphate and sodium sulfate, perform ultrasonic dispersion for 1-2 hours, transfer to a mold for spreading, rolling, stacking, initial setting, demoulding, secondary curing, drying and trimming of four sides to obtain the fireproof board.

9. The processing technology of a multifunctional ceiling according to claim 8, characterized in that: In step B1, the mass ratio of polyethylene glycol monomethyl ether and toluene diisocyanate is 3.4:1; the relative molecular mass of polyethylene glycol monomethyl ether is 650; in step B2, the mass ratio of material E and epoxy resin E51 is 8.8-9.2:0.8-1.2; the epoxide value of epoxy resin E51 is 0.51 mol / 100g.

10. The processing technology of a multifunctional ceiling according to claim 8, characterized in that: In step B3, the mass ratio of tetraethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol, deionized water, and acetic acid is 3-4:1-1.2:2-3:2-3:0.2-0.4; in step B4, the mass ratio of material G, magnesium oxide powder, magnesium sulfate powder, perlite powder, kaolin, polyethylene glycol 2000, and deionized water is 5-8:10-12:8-10:15-18:20-3 0:1-2:40-50; in step B5, the mass ratio of material F, material H, curing agent XY-401, DMP-30 curing agent, animal protein foaming agent, plant adhesive, citric acid, sodium phosphate, and sodium sulfate is 10-15:20-30:0.4-0.6:0.2-0.3:0.1-0.2:1-2:1.2-1.4:0.7-0.9:1-1.2.